Attitude of Parents towards the Girl-Child Education in Biu Emirate, Borno State - Hassan Umar (International Journal of Children, 2025)
This study investigated the attitudes of parents towards girl-child education in Biu Emirate, a region characterized by socio-economic challenges and cultural complexities. Despite global advances in promoting gender equality in education, the Biu Emirate faced significant barriers that impeded educational opportunities for girls. The research aimed to identify the underlying factors influencing parental attitudes, including cultural beliefs, economic constraints, and security concerns. Data were gathered through surveys and interviews with parents, teachers, and community leaders in a variety of rural and urban contexts using a mixed-methods approach. The results showed a range of attitudes, from strong support to deep rejection, which were significantly impacted by socioeconomic level, parental education, and exposure to outside advocacy initiatives. Furthermore, the study emphasized how important regional customs and social mores are in influencing how people view education for girls. It underlined how crucial it is for government agencies, non-governmental groups, and community stakeholders to work together in order to overcome these obstacles. The study emphasized the need for focused interventions to alleviate financial difficulties, raise community awareness, and provide an inclusive learning environment. The study helped create strategic policies and programs targeted at enhancing girl-child education in Biu Emirate by shedding light on the intricate interactions between variables influencing parental views, thereby promoting gender equity and regional development. This all-encompassing strategy can be used as a model to solve comparable issues in other socio-culturally complex areas.
Keywords: Community awareness; cultural beliefs; girl-child education; parental attitudes; socioeconomic challenges